1980
DOI: 10.1007/bf00421979
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Escherichia coli in acute pyelonephritis, acute cystitis and asymptomatic bacteriuria

Abstract: E. coli strains were isolated from urine specimens of hospitalised patients with acute pyelonephritis, acute cystitis or asymptomatic bacteriuria (ABU), and tested for virulence in an experimental mouse model. Of 12 pyelonephritis-strains 11 were shown to be virulent and 1 avirulent; of 12 cystitis-strains 4 were virulent and 8 avirulent; of 12 ABU-strains 5 were virulent and 7 avirulent. It is concluded that, while no difference in virulence was found between cystitis- and ABU-strains, pyelonephritis-strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…None of these differences is so pronounced that it alone could account for this higher prevalence of P. mirabilis. Studies such as those of Brooks et al (1980) and of Van den Bosch et al (1980) have already shown that virulence in these commensal pathogens is a multifactorial phenomenon. Judgement of the contribution of each separate factor to the bacterial virulence is therefore difficult and requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…None of these differences is so pronounced that it alone could account for this higher prevalence of P. mirabilis. Studies such as those of Brooks et al (1980) and of Van den Bosch et al (1980) have already shown that virulence in these commensal pathogens is a multifactorial phenomenon. Judgement of the contribution of each separate factor to the bacterial virulence is therefore difficult and requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The 55 strains of E. coli used in this study were isolated from cases of urinary-tract infection either in general practice or in hospital patients, and were described previously (van den Bosch et al, 1979, 1980a and. Strains AD27 and AD27b were kindly supplied by Dr L. Emody (University of PCcs, Hungary), and were originally numbered P673 and P673/ 1.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study we found differences in virulence between different strains of E. coli in a mouse model (van den Bosch, de Graaff and MacLaren, 1979). We were able to divide the strains into three virulence groups on the basis of the kinetics of the viable counts in the kidney and other organs after intravenous injection, and the measurement of LD50 values and killing times.…”
Section: Introductionmentioning
confidence: 93%
“…A small group with a pattern intermediate between groups II and III was named group IV. Strains isolated from acute pyelonephritis were more often virulent in the mouse model than strains from acute cystitis and from asymptomatic bacteriuria (ABU) (van den Bosch et al 1980a), whereas cystitis strains were not more often virulent than normal faeces strains (van den Bosch et al 1981 a). Therefore we have suggested that E. coli strains reach the bladder in general in proportion to their frequency in the faecal flora and subsequently may invade the kidney and cause serious infection in relation to their virulence.…”
Section: Introductionmentioning
confidence: 97%